Comparative analysis on the thermal performance of selected building materials and technologies for housing in the sudan (Journal of Building and Road Research, 2021)
In search for adequate and affordable housing based on appropriate local building materials and technologies, theNational Fund for Housing and Rehabilitation (NFHR) has invited research institutes, professional associations andpractitioners to give their suggestions and recommendations in this regard. Demonstration models were developed to showthe appropriateness of some technologies and materials and the extent of its affordability.The purpose of this study is to carry out a comparative analysis between some of these different technologies in termsof economical and environmental contexts using Ecotect software. According to the analysis results, selected materialsfor walling and roofing are ranked based on their performance in terms of annual energy required, passive comfort, heatgains, and passive breakdown of heat gains and losses.